Multiresolution angular momentum measurements of z ∼ 1.5−2 star-forming galaxies. Issue 2 (25th September 2021) - Espejo Salcedo, Juan M; Glazebrook, Karl; Fisher, Deanne B; Sweet, Sarah M; Obreschkow, Danail; Swinbank, A M; Gillman, Steven; Tiley, Alfred L
ABSTRACT: We present detailed stellar specific angular momentum ( j * ) measurements of 10 star-forming galaxies at z ∼ 1.5−2, using both high and low spatial resolution integral field spectroscopic data. We developed a code that simultaneously models the adaptive optics (AO) assisted observations from OSIRIS/SINFONI along with their natural seeing (NS) counterparts from KMOS at spatial resolutions of [0.1−0.4] arcsec and [0.6−1.0] arcsec, respectively. The AO data reveal 2/10 systems to be mergers and for the remaining eight the mean uncertainties $\bar{Δ }j_*$ decrease from 49 per cent (NS), and 26.5 per cent (AO), to 16 per cent in the combined analysis. These j * measurements agree within 20 per cent with simple estimates ($\tilde{j_*}$ ) calculated from Hubble Space Telescope photometry and NS kinematics; however, higher resolution kinematics are required to first identify these discs. We find that the choice of surface mass density model and the measurement of effective radius from photometry are the key sources of systematic effects in the measurement of j * between different analyses. Fitting the j * versus M * relations (Fall 1983 ) with a fixed power-law slope of β = 2/3, we find a zero-point consistent with prior NS results at z ≥ 1 within ∼0.3 dex. Finally, we find a ∼0.38 dex scatter about that relation that remains high despite the AO data so we conclude it is intrinsic to galaxies at z > 1. This compares to a scatter of ≤0.2 dex for discs at z ≃ 0 pointing to a settling of the Fall relation with cosmic time.